Knowledge and Technology Transfer in Tourism SMEs - Lopes, João (2020)
This chapter analyzes the dynamics underlying the mechanisms of transfer of knowledge and technology between academia and the tourism industry. Two interviews and research were applied to managers of SMEs. SMEs consider highly educated employees central to the knowledge transfer process, but do not give any incentive to their employees to graduate. It is not always possible to recruit young talents from higher education, as they prefer to go to work for large metropolises. The main barriers for collaboration in R&D academia-industry in the tourism sector are the cost, lack of interest on the part of higher education institutions, and the bureaucratic and time-consuming process. Regarding networking, SMEs agree that they create value, but also consider incorporating a regional innovation ecosystem. SMEs should use a competitive differentiation strategy.